"Solidarity Is Not a Market Exchange": An RM Interview with Robin D. G. Kelley, Part 1. Issue 4 (2nd October 2018) - Kelley, Robin D. G.; Amariglio, Jack; Wilson, Lucas
Abstract : The following is part 1 of an interview with Robin D. G. Kelley, the distinguished UCLA historian. The interview covers the following topics: Kelley's biography of Thelonious Monk, Monk's "surrealism, " and Monk's radical jazz practices; the notions of "authenticity, " "empathy, " and "solidarity" in Kelley's writings; the black freedom struggle since the 1970s; Kelley's relationship to the utopian critiques of black feminism; Kelley's connection to Marxism and the crucial idea of "contradiction"; Kelley's strategic intervention into the intellectual clash between Cornel West and Ta-Nehisi Coates; Kelley's pedagogy of "challenge" versus "confirmation"; Kelley's indebtedness to the work of Cedric Robinson, Robinson's notion of "racial capitalism, " and Robinson's critique of European-based Marxism; Kelley's work in progress on the late journalist Grace Halsell and the role of the Palestinian struggle in her life and Kelley's current politics; and much else.